2017
DOI: 10.1021/acs.macromol.7b01174
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Organization in Calf-Thymus DNA Solutions under Flow in Dependence with DNA Concentration

Abstract: DNA dynamics and flow properties are of great importance for understanding its functions. DNA is a semiflexible polymer chain characterized by having a large persistence length of around 50 nm and high charge density; DNA chains are interacting efficiently at high concentrations, in dependence of the ionic concentration. In relation with DNA molecular characteristics, it is also known that DNA solutions are able to form liquid crystalline phases over a critical polymer concentration. In this work, the supramol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 78 publications
(169 reference statements)
4
15
0
Order By: Relevance
“…Due to condensed counterions in 1-1 electrolytes, there exists a range of distances less than the Debye length where polyions attract each other [6,7,8,9,10]. Birefringence has previously shown that textures corresponding to orientated, ordered domains are induced under shear flow for DNA concentrations higher than 5 mg/mL at low ionic concentration [11]. A schematic representation of the evolution of these solutions at rest and under flow was proposed [11].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to condensed counterions in 1-1 electrolytes, there exists a range of distances less than the Debye length where polyions attract each other [6,7,8,9,10]. Birefringence has previously shown that textures corresponding to orientated, ordered domains are induced under shear flow for DNA concentrations higher than 5 mg/mL at low ionic concentration [11]. A schematic representation of the evolution of these solutions at rest and under flow was proposed [11].…”
Section: Introductionmentioning
confidence: 99%
“…Birefringence has previously shown that textures corresponding to orientated, ordered domains are induced under shear flow for DNA concentrations higher than 5 mg/mL at low ionic concentration [11]. A schematic representation of the evolution of these solutions at rest and under flow was proposed [11]. Understanding the nonlinear behavior of entangled DNA solutions using rheology has been the subject of previous work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Calf thymus DNA shows decreasing viscosity with shear rate and increasing viscosity with temperature 23 . A recent study by Bravo-Anaya et al interprets the observed rheological behaviour as resulting from interacting aggregates of the DNA molecules in flow 22 . The interaction between the DNA molecules is suggested to be driven by H-bonding.…”
mentioning
confidence: 99%
“…It should be noted that DNA does not show the same rheological behaviour as that observed for typical random coil polymers. Typical random coil polymers have conformation that is determined by their entropy and show decreasing viscosity with increasing shear rate and increasing temperature 22,23 . Calf thymus DNA shows decreasing viscosity with shear rate and increasing viscosity with temperature 23 .…”
mentioning
confidence: 99%